The Role of Statins in Disease Modification and Cardiovascular Risk in Rheumatoid Arthritis - Soulaidopoulos, Stergios; Nikiphorou, Elena; Dimitroulas, Theodoros; Kitas, George D. (Frontiers in Medicine, 2018)
Rheumatoid arthritis (RA) is an autoimmune, inflammatory disorder associated with excess cardiovascular morbidity and mortality. A complex interplay between traditional risk factors (dyslipidaemia, insulin resistance, arterial hypertension, obesity, smoking) and chronic inflammation is implicated in the development of premature atherosclerosis and consequently in the higher incidence of cardiovascular events observed in RA patients. Despite the acknowledgment of elevated cardiovascular risk amongst RA individuals, its management remains suboptimal. While statin administration has a crucial role in primary and secondary cardiovascular disease prevention strategies as lipid modulating factors, there are limited data concerning the precise benefit of such therapy in patients with RA. Systemic inflammation and anti-inflammatory treatments influence lipid metabolism, leading to variable states of dyslipidaemia in RA. Hence, the indications for statin therapy for cardiovascular prevention may differ between RA patients and the general population and the precise role of lipid lowering treatment in RA is yet to be established. Furthermore some evidence supports a potential beneficial impact of statins on RA disease activity, attributable to their anti-inflammatory and immunomodulatory properties. This review discusses existing data on the efficacy of statins in reducing RA related cardiovascular risk as well as their potential beneficial effects on disease activity.